Epidemiology of C2 Fractures in the 21st Century: A National Registry Cohort Study of 6, 370 Patients from 1997 to 2014. (17th October 2017) - Robinson, Anna-Lena; Olerud, Claes; Robinson, Yohan
Abstract : Objective . C2 fractures are a common injury in the elderly population. Treatment is often complicated due to osteoporosis and patient comorbidity. This study aims to investigate the incidence and treatment trend of C2 fractures in Sweden. Methods . Patients with the principal and secondary diagnosis of fracture of the second vertebrae (ICD-10: S12.1) between 1997 and 2014 were identified in the Swedish National Patient Registry (NPR). Results . Between 1997 and 2014, 6, 370 patients with a C2 fracture (51% male; age: 72 ± 18 ) were identified in the NPR. The incidence of C2 fractures increased from 3 to 6 per 100, 000 (r = 0.94 ; p < 0.01 ), mainly due to an increase of incidence in the geriatric subgroup (≥70 years). The percentage of surgically treated patients decreased from 1997 to 2014 (r = - 0.80 ; p < 0.01 ). Younger age, male gender, spinal cord injury, and earlier year of admission were associated with surgical treatment assignment. Discussion . This study documents a rising incidence of C2 fractures in the elderly during the last two decades in Sweden. Greater awareness of fractures, improved diagnostics, coding, and a higher activity level of the patients are plausible causes. The declining trend of surgical treatment warrants further study.